2005
DOI: 10.1093/eurpub/cki165
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health in relation to employment status during periods of high and of low levels of unemployment

Abstract: Poorer self-rated health among the unemployed seems to be an increasing public health problem during high levels of unemployment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 30 publications
4
44
0
1
Order By: Relevance
“…Still, we should note that the existence and direction of the moderation effect in these cases remains somewhat questionable. While some studies have found that self-rated health is worse (rather than better) among the unemployed when aggregate unemployment rates are high [65], others have found that both the short-term unemployed and those who remain employed report worse health during recessions [15]. In addition, similarly to the present study, some studies have found no relationship between unemployment rates and self-reported health [14, 66].…”
Section: Discussionsupporting
confidence: 61%
“…Still, we should note that the existence and direction of the moderation effect in these cases remains somewhat questionable. While some studies have found that self-rated health is worse (rather than better) among the unemployed when aggregate unemployment rates are high [65], others have found that both the short-term unemployed and those who remain employed report worse health during recessions [15]. In addition, similarly to the present study, some studies have found no relationship between unemployment rates and self-reported health [14, 66].…”
Section: Discussionsupporting
confidence: 61%
“…Single, widow, separated or divorced displayed significantly poor self-rated health compared to married (or in marital union) individuals [29, 40]. It seems that being married offers a buffer for poor health possibly through greater access to social support and other resources that marriage offers [41]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that the stress caused by unemployment may decrease during economic recession as unemployment is more widespread. Similarly, when unemployment rates are high, the unemployed may be more heterogeneous and healthier (Ahs and Westerling 2006).…”
Section: Discussionmentioning
confidence: 99%